Short-Term Projects versus Adaptive Governance: Conflicting Demands in the Management of Ecological Restoration - Ian Hodge; William M. Adams (Land, 2016)
Drawing on a survey of large-scale ecological restoration initiatives, we find that managers face contradictory demands. On the one hand, they have to raise funds from a variety of sources through competitive procedures for individual projects. These projects require the specification of deliverable outputs within a relatively short project period. On the other hand, ecologists argue that the complexity of ecosystem processes means that it is not possible to know how to deliver predetermined outcomes and that governance should be adaptive, long-term and implemented through networks of stakeholders. This debate parallels a debate in public administration between New Public Management and more recent proposals for a new approach, sometimes termed Public Value Management. Both of these approaches have strengths. Projectification provides control and accountability to funders. Adaptive governance recognises complexity and provides for long-term learning, building networks and adaptive responses. We suggest an institutional architecture that aims to capture the major benefits of each approach based on public support dedicated to ecological restoration and long-term funding programmes.